Experimental Investigation on the Effectiveness of EB-CFRP Confinement of Elliptical Concrete Columns - Benzeguir, Zine (2024)
This paper presents the results of an experimental study involving 20 tests performed on elliptical concrete columns confined with externally bonded carbon fiber-reinforced polymer (EB-CFRP) laminates. The study aimed to evaluate the effects of elliptical aspect ratio (A/B) as well as confinement rigidity (number of EB-FRP layers) on confinement effectiveness. The experimental program consisted of one series of control concrete columns (unstrengthened) and three additional series, each one strengthened with one, two and three layers of EB-CFRP sheets, respectively. Furthermore, each series considered five elliptical aspect ratios (A/B) ranging from 1.0 to 1.6. Following compressive concentric tests until failure, the results were analyzed to characterize the confinement level with an increasing number of EB-CFRP layers as a function of the elliptical aspect ratio. The results show considerable enhancements in compressive strength and in the ductility of the confined columns. Furthermore, this improvement is amplified as the number of EB-CFRP layers increases, indicating a proportional relationship between the compressive strength and the number of CFRP layers. It is found that the ultimate strength of EB-CFRP-confined columns with three layers reached up to 130% compared to the control specimens. However, increasing the elliptical aspect ratio reduced the compressive strength and ductility of confined columns. This study investigated the relation between the CFRP hoop and axial strains and the elliptical aspect ratios. Moreover, through comparison, the results reveal that the prediction models proposed by the Canadian standards S806-12 and S6-19 do not capture the negative effect of the elliptical aspect ratio in confined concrete columns.